Clopidogrel resistance and its effect on clinical outcomes in acute coronary syndrome - Heemanshu Lodhi; Keshavamurthy Ganapathy Bhat; Vivek Singh Guleria; Ratheesh Kumar Janardhana Pillai; Ribhu Goel; Nitin Sharma; Anuka Sharma; Varun Sharma (Indian Heart Journal, 2024)
Aim: The genetic polymorphism of CYP2C19 influences clopidogrel metabolism and resistance. Aim was to assess the association between CYP2C19 loss of function variation, clopidogrel resistance based on platelet reactivity units and clinical outcomes. Methods: A total of 668 patients of Acute Coronary Sundrome (ACS) who underwent Percutaneous Coronary Intervention (PCI) were subjected to genetic screening and 143 patients undrewent platelet function test to study the association between drug metabolization and its effects based on platelet reactivity unit values. Results: Clopidogrel resistance with CYP2C 19 loss of function variation was noted in 54.64% of patients. Clinical outcomes, such as target vessel revascularization, target lesion revascularization, in-stent restenosis, and stent thrombosis, were also studied. Conclusion: CYP2C19 loss of function variation is strongly associated with clopidogrel resistance and adverse clinical outcomes.